АБДУЛЛА ҚОДИРИЙНИНГ “ ЎТКАН КУНЛАР” АСАРИДА ПОРТРЕТ ВА СИФАТЛАШЛАР ТАРЖИМАСИ (Scientific journal of the Fergana State University, 2023)
In this article translation problems of the pictures and epithet of the main characters of the novel “The past days” by Abdulla Kodiriy into German and Russian are investigated. The shortcomings of the translation this novel into Russian and German are analysed. Some mistakes, made by translators, are revealed.